PENGARUH MODAL USAHA DAN KARAKTERISTIK WIRAUSAHA TERHADAP PERKEMBANGAN USAHA PADA CV. DAYA KREASI TEKNOLOGI DI CIKARANG SELATAN - Ridwan Muhsoni; Indra Permana; Etty Zuliawati Zed (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This research was conducted with the aim of knowing whether there are significant differences in the return & risk of cryptocurrencies, stocks, and gold for the 2017-2021 period. This research is quantitative research using a comparative method. The technique used for sampling is a saturated sampling technique taken from the monthly closing price of 60 data from each instrument. The research show that there is a real difference between the risk of bitcoin, stock and gold. This study aims to determine and analyze the Effect of Business Capital, and Entrepreneurial Characteristics, on Business Development at CV. Daya Kreasi Teknologi in South Cikarang. To collect research data using a questionnaire. Sampling using the Non-Probality Sampling technique with the Accidental Sampling technique. The type of research used is quantitative. The population in this study is consumers who buy a Wifi network at the CV. Daya Kreasi Teknologi business. The sample is determined by respondents as many as 100 respondents. Data collection methods used observation, documentation, and questionnaire. The analytical methods Multiple Linear Regression Analysis. Based on the results of the partial study, it shows that there is no significant effect between venture capital on the business development of CV. Daya Kreasi Teknologi. Unlike the case with Entrepreneurial Characteristics which shows a significant influence on the business development